What strategies are used to select patients for direct admission under acute medicine services? A protocol paper for a systematic review of the literature - Elizabeth Sapey; Catherine Atkin; Samuel Evans; Austin Hunt; Georgina Ball; Charlotte Cassidy; Alexander Costley-White; Louise Toy; Rebecca Wilding (BMJ Open)
Introduction Despite unprecedented pressures on urgent and emergency care services, there is no clear consensus on how to provide acute medical care delivery in the UK. These pressures can lead to significant delays in care for patients presenting with emergencies when admitted via traditional routes through the emergency department. Historically, a separate pathway has existed where patients are directly admitted to acute medicine services without attending the emergency department. It is suspected that there is a significant variation in how these patients are selected, triaged and managed in the UK. This systematic review will assess the methods and evidence base used for direct patient admissions to acute medicine services compared with traditional admission pathways through the emergency department.Methods and analysis A systematic review of the literature will be conducted and a total of six databases will be searched: MEDLINE (Ovid), The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE in process, Web of Science, CINAHL and Embase. This will include studies from the period 01 January 1975 to 24 January 2024. Covidence software will be the platform for the extraction of data and paper screening with the selection process reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram. Both title and abstract screening and full-text screening will be done by two reviewers independently. The risk of bias of included studies will be assessed using the methods introduced in the Cochrane Handbook for Systematic Reviews of Interventions and the tool used will be dependent on the type of study. Where possible, outcomes will be dealt with as continuous variables. Change percentage will be assessed between any pathway characteristic or outcome. The χ² test and I² test will be used to evaluate the heterogeneity of included studies. Where appropriate, relevant meta-analysis techniques will be used to compare studies and forest plot produced.Ethics and dissemination This systematic review does not require ethical approval. Findings will be disseminated widely in peer-reviewed publication and media, including conferences.PROSPERO registration number CRD42023495786.